New Insights Toward Nanostructured Drug Delivery of Plant-Derived Polyphenol Compounds: Cancer Treatment and Gene Expression Profiles - Khazei, Keyvan; Mohajeri, Nasrin; Bonabi, Esat; Turk, Zeynep; Zarghami, Nosratollah (Current Cancer Drug Targets, 2021)
The increasing prevalence of cancer has led to expanding traditional medicine objectives for developing novel drug delivery systems. A wide range of plant-derived polyphenol bioactive substances have been investigated in order to explore the anti-cancer effects of these natural compounds and to promote the effective treatment of cancer through apoptosis induction. In this regard, plant-derived polyphenol compounds, including curcumin, silibinin, quercetin, and resveratrol, have been the subject of intense interest for anti-cancer applications due to their ability to regulate apoptotic genes. However, some limitations of pure polyphenol compounds, such as poor bioavailability, short-term stability, low-cellular uptake, and insufficient solubility, have restricted their efficiency. Nanoscale formulations of bioactive agents have provided a novel platform to address these limitations. This paper reviews recent advances in nanoformulation approaches of polyphenolic drugs and their effects on improving the delivery of chemotherapy agents to cancer cells.
Keywords: drug delivery